Emerging Strategies to Overcome Chemoresistance: Structural Insights and Therapeutic Targeting of Multidrug Resistance-Linked ATP-Binding Cassette Transporters - Raghavendra Sashi Krishna Nagampalli; Gangadhar P. Vadla; Eswar Kumar Nadendla (International Journal of Translational Medicine)
The ATP-binding cassette (ABC) transporter superfamily, one of the largest membrane protein families, plays a crucial role in multidrug resistance (MDR) in cancer by mediating the efflux of various chemotherapeutic agents, thereby lowering their intracellular concentrations and diminishing therapeutic effectiveness. Beyond drug efflux, these transporters are also involved in vital biological processes, such as signal transduction in cancer. Over the past few decades, extensive structural and functional research has provided valuable insights into ABC transporters’ broad substrate specificity and transport mechanisms, leading to promising strategies for overcoming MDR. This review will provide a structural understanding of the interactions between ABC transporters and inhibitors to develop novel cancer therapeutics. Additionally, we focus on methods such as irradiation-based immune therapies, thermal therapies, nanomedicine, CRISPR-Cas, and natural therapies that can genetically modify ABC transporters to reduce their expression or reverse the drug efflux ability. Knowledge gained from these approaches can then be translated into the development of new cancer therapeutics that can combat chemotherapy resistance.